A Challenging Case of Groove Pancreatitis - Stenberg, Daniel; ML Lakhani, Midhat, (Journal of Pancreas, 2023)
Groove pancreatitis (GP) is a rare type of segmental chronic pancreatitis that affects the anatomical area between the pancreatic head, the duodenum, and the common bile duct, referred to as the groove area. Most patients with groove pancreatitis are males aged 40–50 years with a history of alcohol abuse. The prevalence of this condition was not determined due to rarity of cases.The clinical symptoms commonly reported were weight loss, upper abdominal pain, postprandial vomiting, and nausea due to duodenal stenosis. It is considered difficult clinically and radiographically to distinguish this form of chronic pancreatitis from other differential diagnoses of inflammatory conditions or malignancies affecting the pancreas or adjacent structures to that groove area. We report a challenging case of GP in an asymptomatic female patient during routine gastric ulcer screening. Our objective is to draw attention to this rare and atypical type of chronic pancreatitis and the importance for early detection on screening EGDs prior to its symptomatic sequelae and complications.
Keywords: groove pancreatitis; pancreatic adenocarcinoma; pancreatic cancer; whipple; endoscopic ultrasound; pancreatitis